Fontes de gordura na dieta de novilhos terminados em confinamento - Metz, Patrícia Alessandra Meneguzzi (2009)
The objective of the present study was to evaluate the effect of the use of different fat sources on feedlot steers finishing diets, on their performance, economic evaluation, carcass and meat characteristics. Twenty steers, with average initial age and weight of 20 months and 260 kg, were used. The offered roughage was corn silage and the tested concentrates were: TCB basic concentrate; TFAI basic concentrate + integral rice bran + rice oil; TM3 - basic concentrate + 3% of fatty acids calcium salts and TM6 basic concentrate + 6% of fatty acids calcium salts. The roughage:concentrate used relation was of 66:34. The dry matter, crude protein, digestible energy, neutral and acid detergent fibers intakes were similar between treatments, as well as average weight gain and final weight (P>.05). However, difference was observed for ether extract daily intake, being the higher value for the animals that consumed 6% of fatty acid calcium salts (.77 kg), intermediary value for the ones that consumed 3% of fatty acid calcium salts and the ones that consumed integral rice bran plus rice oil (.51 kg) and lower value for the ones that consumed basic concentrate (.25 kg). Concentrate and total diet costs, as well as the weight gain necessary to cover feed costs was higher for animals that consumed 6% of fatty acid calcium salts, however gross and net incomes were similar. The animals that consumed 6% of fatty acid calcium salts presented higher subcutaneous fat thickness (5.21 mm) and carcass total fat content (27.9%). Meat characteristics from steers that consumed integral rice bran and oil or fatty acid calcium salts were similar from the ones that didn t consume fat.